BIOLOGICALLY ACTIVE SUBSTANCES OF THE MEDICINAL PLANT ECHINACEA PURPUREA (L.) MOENCH (American Journal of Interdisciplinary Research and Development, 2022)
Currently, the number of medicinal plants subject to scientific research is increasing. Well-known medicinal plants are intensively studied to obtain the most accurate data on the chemical composition, pharmacological effects and safety of use in therapy. Echinacea purpurea (L.) Moench (EP), commonly known as Echinacea purpurea, is a perennial herbaceous flowering plant belonging to the family of compound flowers. The genus Echinacea originates from North America in the United States, and its species are widely distributed around the world. Echinacea has nine different varieties, but only three of them are used as universal medicinal plants: Echinacea purpurea (L.) Moench, Echinacea pallida (Nutt.) and Echinacea angustifolia (DC). Several important groups of biologically active compounds with pharmacological activity have been isolated from Echinacea species. Many beneficial effects of these compounds have been demonstrated.